COVID-19 among migrant farmworkers in Canada: Employment strain in a transnational context - Leah F. Vosko; Tanya Basok; Cynthia Spring; Guillermo Candiz; Glynis George (International Labour Organization (ILO), 2022)
This study analyzes the conditions that migrant farmworkers in Canada endured prior to and during the COVID-19 pandemic (January 2020-March 2022). It draws on policy analysis and open-ended interviews with workers in Canada's Temporary Foreign Worker Program (TFWP), as well as non-status migrants employed in agriculture. It evaluates policies and measures adopted by Canadian authorities to address labour shortages in agriculture and protect the health of migrant farmworkers. In recognizing the intersections of precarious employment and insecure residency status, the study advances an expanded employment strain approach to illustrate how longstanding immigration and labour laws, policies and practices, persisting alongside COVID-19 specific public policy interventions, aimed at improving the quality of and access to job resources for migrant farmworkers, serve to reinforce labour market insecurities confronted by this group of transnational workers. The report offers policy recommendations for improving working conditions, accommodations, and residency status.
Keywords: 330; migrant workers; COVID-19